A Linguistic Analysis of Premchand's Translated Play Shab-Taar - Dr. Mohammad Ifzal But (Zaban-o-Adab, 2024)
Premchand was a notable fiction writer of Urdu literature. He was comely said to be founder of Urdu short story. Realism is a remarkable feature of his literary work. Premchand enjoyed a multisided personality in creative work. He was also good translator. Shab-e-Taar is the translation of Maurice Maeterlinck’s drama “Sightless”. This drama was written in 1891and translated in English in 1911. Following article is about Premchand’s translated drama "Shab-e-Taar". I shall try to describe the drama in the light of linguistics and literature. Although, Premchand had not only good command on short story and novel writing in Urdu and Hindi language but he also had command in English and whereabouts of Persian language. There are seven dramas in his credit, three of those written by the Premchand and four dramas are translated by him in Urdu as well as in English.